Strategi Pengembangan Model Bisnis Klaster Industri Produk Olahan Susu Cipageran - Lukman, Nyayu Rizkita Novelia Mahgalena; Syarief, Rizal; Suparno, Ono (Institut Pertanian Bogor, 2018)
The industrial cluster of dairy products Cipageran Cimahi is a joint organization of several groups engaged in animal husbandry, including dairy farmer groups and dairy processing groups that in carrying out its objectives the organization has not been able to run the business model effectively, so new strategies are needed to improve its business model . The objectives of the research are: (1) to mapping the initial condition of industrial cluster business model of Cipageran dairy products; (2) identifying internal and external factors; (3) to formulate development and improvement strategy in industrial clusters of Cipageran dairy products. The method of analysis in this study used a combination of Business Model Canvas (BMC) approach and the matrix of Strengths, Weakness, Opportunities and Threats (SWOT) in formulating the improvement strategy and business development of industrial cluster of Cipageran dairy products. The results of this study indicate that there should be improvement on each element in Cipageran dairy industry cluster business model. The improvement strategy includes: (1) Developing infrastructure and information technology network; (2) developing the human resources of the cow processing and breeder groups; (3) developing innovation culture by utilizing strong partnership, soul and mentality of high entrepreneurship and good quality according to applicable SOP; 4) to increase the economic value of the dairy cattle industry clusters in terms of leadership capability and legalization of contracts between processors, breeders and consumers.